An independent practitioner's introduction to child and adolescent psychotherapy : playing with ideas - Dowling, Deirdre (Abingdon, Oxon ; New York, NY : Routledge, 2019)
An Independent Practitioner's Introduction to Child and Adolescent Psychotherapy: Playing with Ideas is a comprehensive guide to child and adolescent psychotherapy, taking the practitioner from the initial meeting through the therapeutic process with young people of different ages, to the ending of psychotherapy. It includes approaches to working with parents and the family, introduces theoretical ideas simply and provides references for further learning. Part of the popular Independent Psychoanalytic Approaches series, this book is written from an Independent perspective, but it is also an account of Deirdre Dowling's approach, developed from her considerable experience of working in the NHS and now as a private practitioner. An Independent Practitioner's Introduction to Child and Adolescent Psychotherapy will be an indispensable guide for child psychotherapists (especially trainees), colleagues working in child and family mental health settings, play therapists, counsellors and support staff in schools and child care professionals working therapeutically in residential and community settings.
The therapeutic process -- Creating a therapeutic setting -- Making an assessment and starting the work -- Approaches to child psychotherapy with children of different ages -- Reflections on brief psychotherapy -- Engaging with parents -- Pleasures and challenges of working in a team -- Facing despair, doubt and anger, and finding hope -- Learning from mistakes, losing my way, and the value of supervision -- Working towards an ending -- Behind closed doors : therapeutic work with children and adolescents living with mentally ill and vulnerable parents -- Therapeutic work with children whose parents have separated or divorced -- New pathways : applying psychotherapy to other settings.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
eBooks on EBSCOhost
Keywords: Child psychotherapy; Children; Psychotherapy -- methods; Child; Adolescent; Enfants -- Psychothérapie.; Enfants; children (people by age group); MEDICAL -- Gynecology & Obstetrics; PSYCHOLOGY -- Psychotherapy -- Child & Adolescent; PSYCHOLOGY -- Mental Health; Children; Child psychotherapy